Preparation and Standardization of Mixed Vegetable - Singh, Sauce J P; Nayyer, Md Abu; Kumar, Vinod (Journal of Postharvest Technology, 2014)
The aim of the present work was to utilize the surplus vegetables for the preparation of sauce. For this, a sum of nine treatments combining different vegetables was used to prepare the sauce following the standard method. The vegetable used were potato, carrot, bottle gourd, palak, coriander, green chilli, pumpkin, beetroot, cabbage, cauliflower, and bean. The TSS, total solids, and acidity were increased irrespective of the combination whereas the sensory attributes were tended to decrease during the storage. The combination 5 [pumpkin (28%), beetroot (28%), cabbage (17%), palak (17%), coriander (5%), and green chili (2%)] has been found the best among the all combination and treatments. Considering the organoleptic attributes, the cost benefit ratio of the C5 was 1:2. The results suggest that the unmarketable vegetables could be used for value addition especially during glut to have better remuneration.